CORRELATION COEFFICIENT ANALYSIS AMONG MORPHOLOGICAL CHARACTERS UNDER NORMAL AND TEMPERATURE STRESS IN SOYBEAN (Glycine max L.) - MUSTAFA, W; TARIQ, K; ZAFAR, H; MAJEED, T; KHAN, MI; KHAN, ME; ALI, S; NAZAR, MZK; LATIF, A; KHALIQ, A; SHAMIM, F; HANIF, M (Biological and Clinical Sciences Research Journal, 2023)
The world is facing severe climate change today, mainly due to global warming, a continuous rise in earth’s temperature. Its most striking effect is being felt on agriculture especially in the yield and quality of crop that ultimately threatens the ever-growing population's food security. Like many other crops, soybean, a climate-sensitive crop, is greatly affected by rising temperatures. So, it is the dire need of the hour to develop climate-ready genotype of soybean. That is why research was conducted to check the effect of high temperatures on soybean genotypes and to determine the correlation among morphological traits. After the germplasm collection, two experiments were conducted, one in the laboratory and the other in the wirehouse of the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad, in 2019-2020. Split plot arrangement was made with a Completely Randomized Design and a Randomized Complete Block Design for lab and field experiments, respectively. Three temperature treatments namely To =30ºC (Control), T1 =35ºC and T3 =40ºC were replicated thrice. Data of different morphological traits were recorded and subjected to ANOVA and correlation coefficient analysis. Results of ANOVA for varieties and their interaction with high temperature were significant for most of the traits. Correlation coefficient analysis explained that the No. of leaves/plant, pods/plant, days to 50% flowering and pod setting positively associated with high temperature. On the other hand, seeds/pod and 100-seed weight had a negative correlation with the rise of temperature. The number of leaves and seeds/pod had a positive and significant correlation with 100-seed weight, which means that an increase in these traits would benefit in terms of yield. So, the plant with a higher No. leaves and seeds/pod would be a good criterion for selecting the high-yielding and climate-ready genotype that would benefit in the future against elevated temperature.